2020
DOI: 10.1002/14651858.cd011504.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Community-level interventions for improving access to food in low- and middle-income countries

Abstract: To determine the effects of community-level interventions that aim to improve access to nutritious food in LMICs, for both the whole community and for disadvantaged or at-risk individuals or groups within a community, such as infants and children, women, the elderly, the poor, the unemployed, or minority groups. Secondary objectives To determine the features of community-level interventions that enable or impede the effective implementation of these interventions to improve access to food. To identify unintend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 220 publications
0
33
0
Order By: Relevance
“…In Guatemala, community-based interventions targeting the determinants of child development (and not solely growth) are important but are not considered in our study. 64 , 65 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Guatemala, community-based interventions targeting the determinants of child development (and not solely growth) are important but are not considered in our study. 64 , 65 …”
Section: Discussionmentioning
confidence: 99%
“…In Guatemala, community-based interventions targeting the determinants of child development (and not solely growth) are important but are not considered in our study. 64,65 A final limitation involves the uncertainty of nutrition policy in Guatemala during the COVID-19 pandemic. The Great Crusade was published in February 2020 before the first documented case of COVID-19 in Guatemala.…”
Section: Limitationsmentioning
confidence: 99%
“…Cash transfers, social insurance schemes, and labour market interventions might all improve the livelihoods of those in need by reducing income instability and thereby protecting households from financial shocks. 5 Directly or indirectly, these social protection policies might reduce food insecurity by increasing the amount of money that households have to spend on food. 6 However, not all of these policies will necessarily improve food security to the same degree and so some have suggested that these programmes must target the households that are most vulnerable to most effectively impact food insecurity.…”
Section: Introductionmentioning
confidence: 99%
“…In Guatemala, community based interventions targeting the determinants of child development (and not solely growth) are important but are not considered in our study. 62,63 A final limitation involves the uncertainty of nutrition policy in Guatemala during the COVID-19 pandemic. The Great Crusade was published in February 2020 before the first documented case of COVID-19 in Guatemala.…”
Section: Discussionmentioning
confidence: 99%